Praça espaço de registro histórico e cultural - Fiss, Bruna Kisathowski (2020)
This research was developed with a link in line of Culture, Educative Process and Teachers Formation of the Education Master’s at Universidade Estadual do Oeste do Paraná (UNIOESTE) and with the Research Group Representations, Spaces, Times and Languages in Educational Experiences (RETLEE). The objective was analyze the square Dr Educardo Virmond Suplicy (EVS) function, located in central region of Francisco Beltrão municipality, for it a space of intense mobility and people concentration. We study the constitution this space, your historic trajectory and relationship of the users with the elements that compose your structure. The research was characterized for a case study and the investigative instruments was questionnaire, interviews, observation, field diary, photographic records, documents, data collection in a newspaper and bibliography too. With evidence in some authors as: Mumford (1982), Weimer (2012), Caldeira (2007), Sennett (1995), Borges (2008) and Bakhtin (1999), in origin survey, of history and in timeline. Santos (2017) underpins the factors that produce the space as: process, structure, shape and function. The elements that date back to municipality history and Square contextualization, in Lazier (2004), Battisti (2006), Galvão (2009), Poli (2009), Silva A. (2010), Silva R. (2013). In data collection, in general, a local newspapers, especially in Jornal de Beltrão. The text follows conceptual support in Gomes (2013), in exposure place as inductor of view and of see. In Harvey (2014) defend the public democratic spaces and, in Santos (2014; 2008) that conceptualize the place, landscape and nature. We treat about the Patrimonial Education with Marchette (2016). We carried through an action of the monument study with academics of Universidade Aberta para a Terceira Idade (UNATI), with students of the Colégio Estadual Industrial (CEI) and Colégio Estadual Dr. Eduardo Virmond Suplicy (CES). Therefore Callai (2004, 2016) and Claudino (2019) they emphasize the importance of the place study and citizen formation. The Square modify over time, but not dissolve and is related the social movement, since its beginning to the present time. Therefore have efforts of public power into ensure this territory to the population. It’s represent the history and contradictions of society, which it arise. Your materiality records the history and culture of social groups. This factor enable by means of your study, the citizen formation that know the lively place.